Criminal Sanctions’ Reformulation in the Reclamation of the Mining Community - Faisal Faisal; Derita Prapti Rahayu; Yokotani Yokotani (Fiat Justisia, 2022)
The norm of sanctions outlined in the 2020 Mining Law, shaped by irrational legislative policies, can lead to criminal disparities and contribute to criminogenic factors. This research emphasizes the need for reformulation of sanctions related to reclamation obligations within the community mining category. The primary aim is to realign the rationale behind criminalizing post-mining reclamation responsibilities. The discussion centers on reformulating provisions specifically for the reclamation obligations of community mining. Employing normative legal research methods, the study identifies the reclamation obligation sanction as an omission offense, characterized as both a passive and formal crime. The proposed reformulation is grounded in the principle of balancing a double-track system of sanctions, where criminal penalties serve as a last resort if action sanctions are disregarded. Action sanctions are prioritized to focus on restoring post-mining environmental conditions, and it is recommended that criminal sanctions and fines within the community mining category be less severe to encourage compliance and sustainability.